Local Outdoor Advertising SMEs Survival in China - Chen, Li (2007)
In the past 20 years, advertising has become one of the industries with unprecedented high development speed in China. The Chinese Economic Reform that was started in 1978 brought an innovative opportunity to develop Chinese economy. The boom of economy stands for the incredible fast growth of all the industries in China. As an industry which provides the service to all the other industries, advertising industry also seems will have a superior prospect. However, since advertising industry was entirely opened follow the agreement of WTO in 2005, the rivalry in this industry has become much more intensive. International advertising giants are trying to expand their territory in this high-potential market one after another. The survival of Chinese local advertising enterprises has been being threatened in current market, especially those small-scale and med-scale of enterprises. In recent two years, the growth of this industry distinctly decelerated. More and more problems appeared. The disorder of Chinese ads market was revealed.